Diminished treatment response in relapsed versus first-episode schizophrenia as revealed by a panel of blood-based biomarkers: A combined cross-sectional and longitudinal study. (October 2022) - Cai, Hualin; Zeng, Cuirong; Zhang, Xiangyang; Liu, Yong; Wu, Renrong; Guo, Wenbin; Wang, Jianjian; Wu, Haishan; Tang, Hui; Ge, Xiaoping; Yu, Yan; Zhang, Shuangyang; et al.
Highlights: Investigated biochemical underpinnings of diminished antipsychotic response in relapsed versus first-episode schizophrenia. Used a combined cross-sectional and longitudinal clinical study design with 707 schizophrenia patients. Reduced antipsychotic response due to relapse was revealed by neurosteroid, phospholipid and purinergic metabolisms. Inosine and progesterone were identified as potential predictive biomarkers for treatment response. Abstract: There is a paucity of biomarkers for the prediction of treatment response in schizophrenia. In this study, we aimed to investigate whether diminished antipsychotic treatment response in relapsed versus first-episode schizophrenia can be revealed and predicted by a panel of blood-based biomarkers. A cross-sectional cohort consisting of 655 schizophrenia patients at different episodes and 606 healthy controls, and a longitudinal cohort including 52 first-episode antipsychotic-naïve schizophrenia patients treated with the same antipsychotic drugs during the 5-year follow-up of their first three episodes were enrolled. Plasma biomarker changes and symptom improvement were compared between the drug-free phase of psychosis onset and after 4 weeks of atypical antipsychotic drug (AAPD) treatment. In response to treatment, the extent of changes in the biomarkers of bioenergetic, purinergic, phospholipid and neurosteroid metabolisms dwindled down as number of episode and illness duration increased in relapsed schizophrenia. The changes of creatine, inosine, progesterone, allopregnanolone, cortisol and PE(16:0/22:6) were significantly correlated with the improvement of symptomatology. Inosine and progesterone at baseline were shown to be strong predictive biomarkers of treatment response. The results suggest that AAPD treatment response is diminished in the context of relapse, and our findings open new avenues for understanding the pathophysiology of treatment-resistance schizophrenia.